Muzzle characteristics in the dermatoglyphics of muzzle of different breeds of cattle - MISHRA, SHARAD; TOMER, O S; KALM, E (The Indian Journal of Animal Sciences, 2013)
Dermatoglyphics of muzzle in 6 breeds of cattle, viz. Tharparkar, SahiwaJ, Karan Swiss, Karan Fries, Red and White, and Black and White, were studied to find out the; breed differences in terms of muzzle characteristics. The differences in beads at base sector and at middle sector among/Tharparkar, Sahiwal and Karan Swiss were nonsignificant. The characteristics were significantly (P<0.05) different in Karan Fries from those ofTharparkar, Sahiwal, Karan Swiss, Red and White, and Black and White breeds of cattle. The Red and White, and Black and White breeds of Germany contained less number of beads at the base, middle and upper sectors of the muzzle and differed significantly (P<0.05) from Indian breeds of cattle. However, there was no significant difference between Red and White, and Black and White breeds. The beads of the upper sector among Tharparkar, Sahiwal and Karan Fries were similar. The beads of the upper sector of Karan Swiss were similar to that of Sahiwal but significantly (P<0.05) higher than ofTharparkar, Karan Fries, Red and White and Black, and White breeds. The right and left pattern ridges in Black and White., Red and White, Karan Fries and Sahiwal breeds were similar, however, differed significantly from Tharparkar and Karan Swiss breeds. The number of ridges at base sector in Black and White cattle were significantly (P<0.05) higber than in Sahiwal and Karan Swiss. German breeds of cattle contained significantly (P<0.05) more number of ridges in the middle sector and number of ridges in right and left halves than all Indian breeds. The number of right and left pattern ridges were nonsignificantly different among all breeds. Whereas, there was significant (P<0.05) difference in the number of total pattem ridges between Karan Fries and Black and White breeds. It was concluded that muzzle characteristics can be used as one of the methods for breed characterization.